Investigation of the Modulation of the Tidal Stream Resource by Ocean Currents through a Complex Tidal Channel - Alice J. Goward Brown; Matt Lewis; Benjamin I. Barton; Gus Jeans; Steven A. Spall (Journal of Marine Science and Engineering, 2019)
Tidal energy has the opportunity to bring reliable electricity to remote regions in the world. A resource assessment, including the response of the tidal stream resource to fluctuations in the Indonesian Through Flow (ITF) is performed using the Regional Ocean Modelling System (ROMS) to simulate four different scenarios for flow through the Lombok Strait in Indonesia. Tidal currents simulated with a variable ITF are compared against a tide-only (TO) simulation to identify how the ITF spatially changes the resource across the Lombok Strait. We find that the uncertainty in the tidal currents from the TO simulation is 50% greater than the variable ITF simulation. To identify change to resource, surface velocities from Strong ITF and Weak ITF scenarios are considered. As a result of the fluctuations in the ITF, certain characteristics, such as the asymmetry and magnitude, of the tidal current vary greatly. However, the magnitude of change is variable, with regions to the west of the strait experiencing greater modulation than in the east, suggesting that resource uncertainty can be minimised with selective site positioning.